If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + -1 = z + 8 + -22 Reorder the terms: -1 + 2z = z + 8 + -22 Reorder the terms: -1 + 2z = 8 + -22 + z Combine like terms: 8 + -22 = -14 -1 + 2z = -14 + z Solving -1 + 2z = -14 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. -1 + 2z + -1z = -14 + z + -1z Combine like terms: 2z + -1z = 1z -1 + 1z = -14 + z + -1z Combine like terms: z + -1z = 0 -1 + 1z = -14 + 0 -1 + 1z = -14 Add '1' to each side of the equation. -1 + 1 + 1z = -14 + 1 Combine like terms: -1 + 1 = 0 0 + 1z = -14 + 1 1z = -14 + 1 Combine like terms: -14 + 1 = -13 1z = -13 Divide each side by '1'. z = -13 Simplifying z = -13
| x+91=x+971 | | x^2-22xy-48y^2= | | x/4-10=-13 | | -3+11-7n=-13 | | 6c-12+4c=8c | | -3+9=a | | 81-(6*9)=1 | | 19f^2-17k-2=0 | | 3s-4+6s+7= | | 18x^2+9x-20=0 | | d^2-14d+13=0 | | -6/5=a | | 16x-5=105 | | -5(4r+8)=16-3r | | (7x+2)(3x^3-14x-5)=0 | | 7x=434 | | 12+1234567890=x(43+83) | | -5-3x=-4x-8 | | 3m^2-13m+12=0 | | 312+2y=36 | | 13=-2-5x | | 16=2x-2 | | -3(2+5y)=-26 | | 4(b-2)=2(2c+2) | | 2x-6=12+11x | | -.5=6-.66x | | -8c-12+11c=12 | | 30=-2x+8 | | 44=-4-6a | | 8(v-5)=6v-18 | | X^2+19=8x | | 1+8x+5-4x=10 |